2002
DOI: 10.1046/j.1365-2141.2002.03734.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis of 1,25(OH)2D3‐dependent differentiation of HL‐60 cells: a cDNA array study

Abstract: Summary. The alterations in gene expression associated with 1,25(OH) 2 D 3 -induced differentiation of HL-60 cells were studied in order to identify potential targets for further investigation of the genetic basis of acute myeloid leukaemia. Atlas human haematology filters, including 406 genes (Clontech), were used to study gene expression in response to 1,25(OH) 2 D 3 (concentration, 5 · 10 )8 mol/l) for 24 and 72 h. Compared with untreated cells, expression differences were found in 43 genes. Downregulated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…Other chemokines (MIP-3, MIP-4, MIP-1A, BCA-1, CC-1, MCP-1, TAFA-5, IP-9, CXCR4) were not identified on this network, but they were up-regulated in our study. The CXCR4 gene was reported as up-regulated in leukemia and PCA before (Savli et al, 2002;Engl et al, 2006;Ao et al, 2007). Akashi et al showed that the expression of androgen receptor (AR) down-regulates the migratory responses of human PCA cells via chemokine and its receptor systems (Akashi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other chemokines (MIP-3, MIP-4, MIP-1A, BCA-1, CC-1, MCP-1, TAFA-5, IP-9, CXCR4) were not identified on this network, but they were up-regulated in our study. The CXCR4 gene was reported as up-regulated in leukemia and PCA before (Savli et al, 2002;Engl et al, 2006;Ao et al, 2007). Akashi et al showed that the expression of androgen receptor (AR) down-regulates the migratory responses of human PCA cells via chemokine and its receptor systems (Akashi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR were performed using a LightCycler (Roche) as reported previously (Savli et al, 2002) for determination of Fas, IL-1β, P21, and CXCR4 gene expressions. β2-microglobulin gene was used as the internal control.…”
Section: Quantitative Real-time Pcr (Q-rt-pcr)mentioning
confidence: 99%
“…Differentiation results in DEK downregulation in human promyelocytic HL-60 cells and in human foreskin keratinocytes, and in turn, overexpression of DEK counteracts cell differentiation (Savli et al, 2002;Wise-Draper et al, 2009b) and promotes proliferation and transformation of epithelial cells (Wise-Draper et al, 2009a). The DEK gene was originally described during early embryonic development, but is preferentially expressed in actively proliferating cells and can inhibit cell differentiation, senescence, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…6). The most important examples encompass primary, immortalized, or malignant prostate , Kovalenko et al 2010, Wang et al 2011, colon , squamous cell carcinoma (Akutsu et al 2001, Lin et al 2002, myelocytic/monocytic leukemia (Savli et al 2002, Suzuki et al 2006, Heikkinen et al 2011, ovarian , coronary artery smooth muscle (Wu-Wong et al 2006), (pre-) adipocytic (Sun et al 2008), lymphoblastoid (Ramagopalan et al 2010), or breast cancer (Swami et al 2003, Kriebitzsch et al In silico prediction of putative VDR-RXR heterodimer binding sites within the promoter regions of RTq-PCR-validated calcitriol target genes. Columns specify applied matrix concepts, relative position/orientation with respect to the relevant TSS, calculated statistics, and matching consensus motifs.…”
Section: Discussionmentioning
confidence: 99%